2021
DOI: 10.1159/000518415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Primary Care Providers’ Readiness for Delivering Genetic and Genomic Services to Underserved Populations

Abstract: <b><i>Introduction:</i></b> Increased genomics knowledge and access are advancing precision medicine and care delivery. With the translation of precision medicine across health care, genetics and genomics will play a greater role in primary care services. Health disparities and inadequate representation of racial and ethnically diverse groups threaten equitable access for those historically underserved. Health provider awareness, knowledge, and perceived importance are important determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…81,106,109 The difficulties around genetic test interpretation can be exacerbated when providing care to people who are underrepresented in health care. 87 The potential for incidental and secondary findings (that is, additional information that may not be directly related to the reasons testing was undertaking), and their implications for patients and family members, adds to the complexity of testing.…”
Section: Complexity In Interpreting Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…81,106,109 The difficulties around genetic test interpretation can be exacerbated when providing care to people who are underrepresented in health care. 87 The potential for incidental and secondary findings (that is, additional information that may not be directly related to the reasons testing was undertaking), and their implications for patients and family members, adds to the complexity of testing.…”
Section: Complexity In Interpreting Test Resultsmentioning
confidence: 99%
“…• Enhancing diversity, inclusivity, and engagement: Increasing diversity in health professionals through workforce planning and education may help mitigate health concerns and create more inclusive care. 87 Other examples include the codesign (i.e., active partnering and engagement) of precision medicine health services with equity-deserving and underrepresented groups, and ongoing data collection related to disparities in access to and outcomes of precision medicine 13,88,89 Increased Demands on Health System Capacity and Infrastructure From the Use of Precision Medicine…”
Section: Top Issues About Precision Medicine Technologies To Watch In...mentioning
confidence: 99%
“…Because of precision medicine's relative novelty, there also is a lack of familiarity with how to integrate pharmacogenetic and genetic findings into primary care. For example, many FQHCs currently lack the ability to integrate such findings into EHRs [24]. Another study found that primary care providers "consistently report feeling unprepared to use pharmacogenetic data and cite a lack of point-of-care resources for applying test results in practice" [25].…”
Section: Obstacles To Follow-up Medical Servicesmentioning
confidence: 99%
“…The lag in the clinical adoption of genomic interventions, including population screening, into routine clinical practice has been attributed to various factors related to the impending shift from genetic specialty providers to primary care providers, including contextual factors (e.g., a perceived lack of knowledge, expertise, and supporting resources) and process factors (e.g., an engagement of organizational leadership and provider buy-in) [ 22 , 23 , 24 ]. The development of educational and clinical decision support tools for non-genetics clinicians is growing; however, research to develop and evaluate strategies to effectively integrate genomic screening into diverse clinical settings is largely unexplored, particularly in settings with limited resources and other structural barriers to implementing public health innovations [ 25 , 26 ]. Engagement with clinical providers and staff will be needed to develop and provide resources to support the integration of ABGS into the clinical workflow.…”
Section: Introductionmentioning
confidence: 99%